Non-traditional security in Asia issues, challenges, and framework for action - Caballero-Anthony, Mely; Cook, Alistair D.B (Institute of Southeast Asian Studies, 2013)
Non-Traditional Security in Asia examines the critical security challenges faced by states and societies in Asia including health, food, water, natural disasters, internal conflict, forced migration, energy, transnational crime, and cyber security. Through the development of a comprehensive analytical framework that establishes the key ingredients to policy evaluation, the editors draw on a wide variety of experts to collaborate in investigating these crucial issues. This inclusive framework ensures that all voices are heard including those oftentimes under-represented and marginalized in society to ensure that academic and policy debates are well informed about the often complex and nuanced nature of these non-traditional security challenges. Through an investigation into these specific non-traditional security threats, Non-Traditional Security in Asia documents and evaluates many of the most pressing challenges faced by Asia today. The authors analyse the ways in which particular issues are addressed by the many stakeholders involved in the policy-making process, both within governments and across societies. The question of how these challenges are addressed across and between the different levels of global governance highlights the strengths and weakness that are directly attributable to policy successes and failures. It is through this layered and comprehensive approach, together with an evaluation of the role of stakeholders, which binds together the chapter contributions to this collection. The book undertakes an issue-specific chapter study of how Asian states and societies address these non-traditional security concerns from environmental adaptation and mitigation measures to conflict resolution. For each issue area, it identifies and explains the concerns of various policy communities, identifying the motivations behind some of the key decisions made to affect change or stabilize the status quo. Essentially it questions not only what a security issue is but also for whom the issue is important and the interaction this has with policy outcomes. With a focus on regional and global institutions as well as national and local ones, this collection illustrates the variety of stakeholders involved in non-traditional security concerns, and reflects on their relative importance in the decision-making process. Through a systematic evaluation of these non-traditional security issues by employing a comprehensive analytical framework, critical appreciation of the dynamics of the policy-making process surrounding issues of crucial national, regional and international significance in Asia are made. As a result of sharing these insights, the contributors provide the tools as well as a selection of issue-specific stakeholders to illuminate the key but complex characteristics of non-traditional security in Asia.